2005
DOI: 10.1007/s00464-004-2257-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted pelvic organ prolapse surgery

Abstract: Our experience indicates that using the da-Vinci robotic system is feasible, safe, and effective for the treatment of pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 21 publications
5
50
1
7
Order By: Relevance
“…The surgical procedure performed to place the anterior mesh in this series was similar to other authors' description [12] . We have chosen Y-shaped polypropylene meshes covered by acellular collagen, in order to make them more biocompatible trying to reduce the risk of mesh extrusion.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The surgical procedure performed to place the anterior mesh in this series was similar to other authors' description [12] . We have chosen Y-shaped polypropylene meshes covered by acellular collagen, in order to make them more biocompatible trying to reduce the risk of mesh extrusion.…”
Section: Discussionmentioning
confidence: 53%
“…We have chosen Y-shaped polypropylene meshes covered by acellular collagen, in order to make them more biocompatible trying to reduce the risk of mesh extrusion. Vaginal mesh extrusion and erosion have been described as postoperative complications by other authors [10,12] . There were no mesh extrusions in this series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of sacrocolpopexy are similar to those obtained by open surgery. The robot is especially useful for better visualization and handling in the presacral region, as well as in the insertion of a mesh and its secure fixation to the vaginal stump, the cervical stump, or the presacral area (15). Re-anastomosis of the fallopian tubes for the purpose of refertilization is associated with a success rate of 67.6% in open surgery, and a 5.6% incidence of ectopic pregnancies.…”
Section: Application In Benign Gynecological Diseasesmentioning
confidence: 99%
“…They concluded that using the da Vinci robotic system is feasible, safe and effective for the treatment of pelvic organ prolapse. 117 Robot-assisted rectovaginopexy was described in 15 women by Draaisma et al 118 Median set-up robot time was 10 minutes, and median skin-to-skin operating time was 160 minutes, median blood loss less than 50 ml and median hospital stay was 4 days. Two other small series of six and ten women also showed the feasibility of this procedure.…”
Section: Pelvic Surgery (Urogynaecology)mentioning
confidence: 99%